Polysalicylic Acid Polymer Microparticle Decoys Therapeutically Treat Acute Respiratory Distress Syndrome (Adv. Healthcare Mater. 7/2022). Issue 7 (6th April 2022) - Brannon, Emma R.; Kelley, William J.; Newstead, Michael W.; Banka, Alison L.; Uhrich, Kathryn E.; O'Connor, Colleen E.; Standiford, Theodore J.; Eniola‐Adefeso, Omolola
Abstract : Lung Injury In article number 2101534 by Omolola Eniola‐Adefeso and co‐workers, acute respiratory distress syndrome (ARDS) is often characterized by the abrupt accumulation of activated neutrophils in the lungs. Particle‐based therapeutics can serve as a novel ARDS treatment that diverts rogue neutrophils in the systemic circulation, preventing neutrophil‐related organ damage. Furthermore, materials used to fabricate particle‐based therapeutics can be optimized to modulate cell phenotypes and, ultimately, the inflammatory response.